SIBLING RIVALRY AS REFLECTED IN JULIE ANNE PETERS LUNA - NUR PARWATI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2019)
AbstractSibling Rivalry is a competition among sibling to get the parents’ affection. In the novel, Liam is the oldest child in his family and his personality of sibling rivalry can be seen from his daily behavior toward people around him. The aim of this analysis is to find out the indications of sibling rivalry appear among Bristow’s children especially Liam O’Neill and the impact of sibling rivalry toward Liam’s life. The object of this study is a novel written by Julie Anne Peters’ entitled Luna which was published on April, 2013. The main conflict told in this novel is about rivalry or competition among Bristow’s children that is especially caused by the feeling of jealousy by Liam O’Neill. This study uses the concept of sibling rivalry according to the psychoanalysis theory. The result of the study shows that Liam indicates his personality of sibling rivalry toward his sister. He showed his jealousy and sibling rivalry toward his sister when he was a childand also adolescent. In the end, this study finds that the impact of sibling rivalry could be negative and possitive impact. Keywords : sibling rivalry, jealousy, family environtment